Difference-Difference Synchronizations of Chaotic and Hyperchaotic Systems - Dongmo, Eric Donald; Ojo, Kayode Stephen; Woafo, Paul; Njah, Abdulahi Ndzi (Journal of Applied Nonlinear Dynamics, 2026)
This paper investigates a new synchronization Difference-Difference Synchronization (DDS), based on drive response configuration via the active backstepping technique. In this new synchronization scheme, the difference between the state variables of two master systems synchronizes with the difference between the state variables of two response systems. The proposed DDS scheme is investigated using four chaotic systems and four hyperchaotic systems evolving from different initial conditions. The analytical and numerical simulations show the feasibility and the effectiveness of the proposed synchronization scheme.